Arhitektura prostomih informacijskih sustava - Grbavac, Vitomir (Promet - Traffic&Transportation, 2012)
This paper deals with the architecture of space information systems. These systems make part of the information science discipline: the space information science, dealing with compilation, processing, storing to memory and dissemination of space-related information within the scope of successful and effective making use of land, being itself a major national resource. Detailed review covers all contents of information system which in the majority of progressive nations make part of a separate scientific discipline of space information science.